Impact of tofacitinib treatment on human B-cells in vitro and in vivo. (February 2017) - Rizzi, Marta; Lorenzetti, Raquel; Fischer, Kathleen; Staniek, Julian; Janowska, Iga; Troilo, Arianna; Strohmeier, Valentina; Erlacher, Miriam; Kunze, Mirjam; Bannert, Bettina; Kyburz, Diego; Voll, Reinhard E.; et al.
Abstract: B-cells are pivotal to the pathogenesis of rheumatoid arthritis and tofacitinib, a JAK inhibitor, is effective and safe in its treatment. Tofacitinib interferes with signal transduction via cytokine receptors using the common γ-chain. Despite extensive data on T-lymphocytes, the impact of tofacitinib on B-lymphocytes is poorly understood. In this study we assessed the effect of tofacitinib on B-lymphocyte differentiation and function. Tofacitinib treatment strongly impaired in vitro plasmablast development, immunoglobulin secretion and induction of B-cell fate determining transcription factors, Blimp - 1, Xbp - 1, and IRF - 4, in naïve B-cells. Interestingly, class switch and activation-induced cytidine deaminase ( AICDA ) induction was only slightly reduced in activated naïve B-cells. The effect of tofacitinib on plasmablast formation, immunoglobulin secretion and proliferation was less profound, when peripheral blood B-cells, including not only naïve but also memory B-cells, were stimulated. In line with these in vitro results, the relative distribution of B-cell populations remained stable in tofacitinib treated patients. Nevertheless, a temporary increase in absolute B-cell numbers was observed 6–8 weeks after start of treatment. In addition, B-cells isolated from tofacitinib treated patients responded rapidly to in vitro activation. We demonstrate that tofacitinib has a direct impact on human naïve B-lymphocytes, independently from its effect on T-lymphocytes, by impairing their development into plasmablasts and immunoglobulin secretion. The major effect of tofacitinib on naïve B-lymphocyte development points to the potential inability of tofacitinib-treated patients to respond to novel antigens, and suggests planning vaccination strategies prior to tofacitinib treatment. Highlights: B-cells are pivotal in pathogenesis of rheumatoid arthritis and are activated via common γ-chain cytokine receptors. Tofacitinib, a JAK inhibitor, inhibits plasmablast development and antibody secretion from naive B-cells. Treatment with tofacitinib may impair immune responses to new antigens. Vaccination against new antigens prior to tofacitinib treatment should be considered. Tofacitinib does not influence the proportion of B-cell subpopulations but their absolute numbers in vivo .